STRATEGI PEMBELAJARAN MASA PANDEMI COVID-19 STIT AL-IBROHIMY BANGKALAN - Muhammad Fauzi (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2020)
The Covid-19 virus outbreak has a very broad impact in the joints of life, including the education sector. So that the government implements an Education policy in an Emergency Period for the Spread of the Corona Virus. This is in anticipation of the spread of the corona virus in schools and colleges. One of the points emphasized by the government is that learning carried out in schools and colleges is transferred to online learning at home. Learning is carried out from home using a laptop, computer, or smartphone accompanied by various applications that support the learning process. However, online learning that has been implemented since the Covid-19 pandemic, has had several problems faced by students and educators. We do not realize that the theory of learning strategies so far is mostly only concerned with the conventional (face-to-face) learning process. So that when there is an emergency phenomenon, the learning strategy will not run effectively and efficiently. Here, distance learning using online media is felt by the community to be burdensome for students by allocating special funds for purchasing expensive packages. Responding to such problems, the STIT al-Ibrohimy campus implemented government recommendations and also considered the condition of the Galis community with community-based online and offline learning process methods. The community-based learning process here is to provide MiFi assistance to students to be used to study in groups in a predetermined place while still paying attention to health protocols.